Eosinophilic Angiocentric Fibrosis of the Subglottis. (23rd August 2013) - Kraft, Shannon M.; Patel, Neil; Sauer, David; Hamilton, Bronwyn; Schindler, Joshua S.
Abstract : Objectives: Eosinophlic angiocentric fibrosis (EAF) is a rare disorder that belongs to the spectrum of IgG4‐related diseases (IgG4‐RD). We review a case of EAF presenting as a subglottic stenosis. Methods: We discuss the pertinent clinical, radiographic, and histological findings, demonstrating the diagnostic challenges associated with EAF. We review the literature on respiratory tract EAF and discuss the associated management dilemmas when this otherwise benign disease affects critical structures. A 44 year‐old female presented a twelve‐month history of progressive dyspnea and stridor. A pulmonary function test (PFT) showed flattened inspiratory and expiratory flow loops suggestive of subglottic stenosis. Pre‐operative computed tomography (CT) revealed a subglottic mass with cricoid erosion. During endoscopy, a submucosal lesion was noted to involve the conus elasticus and cricoid. The airway was temporized with CO2 laser resection of the mass and dilation. Results: Histology showed an inflammatory infiltrate composed of lymphocytes, plasma cells, and eosinophils. Fibrosclerosis was organized around thickened vessels in an onionskin pattern. Immunohistochemical revealed a minor IgG‐4 plasma cell component. Staining was negative for beta‐catenin and ALK‐1. The specimen was found to be consistent with EAF. Serum IgG‐4 was mildly elevated at 117 mg/dL. The patient has been managed with oral steroids, and her airway remains stable. Conclusions: EAF is a subtype of inflammatory fibrosclerosis that belongs in the spectrum of IgG4‐RD. Most commonly reported in the orbit or sinonasal tract, EAF lesions of the laryngotracheal complex are exceedingly rare. Although benign, EAF pseudotumors can be locally destructive, requiring a multidisciplinary approach to care.